Bioaccumulation of Lead (Pb) on The Dog Conch (Strombus canarium) in Madong Waters, Tanjung Pinang - Tirtama, Wahyu; Bengen, Dietriech Geoffrey; Rastina, Rastina (Universitas Diponegoro, 2024)
The waters of Madong in Tanjung Pinang city are located in a strategic area that has a significant impact on the livelihoods of fishermen, post-bauxite mining areas, ship traffic, and population activities. These factors have contributed to the contamination of heavy metal Pb in the waters, sediments, and dog conch. The purpose of this study is to analyze the levels of heavy metal Pb in the waters, sediment, and dog conch, and to assess the bioaccumulation factors of heavy metal Pb in dog conch in Madong waters. Samples of waters, sediment, and dog conch were collected from three stations and analyzed using AAS at the Marine Chemistry Laboratory of Raja Ali Haji Maritime University. The concentration of Pb in the waters ranged from 0.0204 mg/L to 0.0636 mg/L, while the concentration of Pb in sediment ranged from 0.5947 mg/Kg to 0.9402 mg/Kg. The Pb metal concentration in juvenile dog conch ranged from 0.0745 mg/Kg to 0.3437 mg/Kg. The highest BAF and BSAF values for Pb metal in adult dog conch were observed at station 1, with values of 27.241 and 0.6991, respectively. The categorization of Pb metal in Strombus canarium dog conch as low is based on the BAF and BSAF value categories.